Combined free flaps with arteriovenous loops for reconstruction of extensive thoracic defects after sternal osteomyelitis - Taeger, Christian; Horch, Raymund E.; Arkudas, Andreas; Schmitz, Marweh; Stübinger, Axel; Lang, Werner; Meyer, Alexander; Seitz, Tatjana; Weyand, Michael; Beier, Justus (Microsurgery, 2016)
Various local flaps have been described for patients suffering from sternal osteomyelitis and are regarded as a standard procedure for defect reconstruction. In contrast, the use of microsurgical free flaps has been reported anecdotally only. We present our experiences with the combination of an arteriovenous loop and a free flap transfer in defects larger than half of the sternum.Between January 2012 and October 2014, eight patients with a mean age of 68 years who suffered from extensive deep sternal osteomyelitis were operated in a consecutive series. After radical surgical debridement, the defect size comprised all three thirds of the sternum. Defect reconstruction was achieved by means of free flap transplantation using the vastus lateralis myocutaneous flap, rectus abdominis, and bipedicled latissimus dorsi/parascapular flap. As local recipient vessels were depleted in all patients, the pedicle of the flap was anastomosed to a high-flow and short-length subclavian arteriovenous loop as recipient vessel in all cases.The immediate postoperative course in all patients was uneventful despite one axonal injury to the femoral nerve at the donor site. There was no partial or total flap loss. During a mean follow-up of 9 months, one patient suffered from a local infection at the donor site. In all patients, a successful defect reconstruction could be achieved.Depletion of local recipient vessels as an obstacle for free flap reconstruction can be overcome by creating an arteriovenous loop. Even extensive defects are adequate for defect reconstruction using a single or, in extreme cases, bipedicled free flap. © 2015 Wiley Periodicals, Inc. Microsurgery 36:121-127, 2016.
EVALuna2:15222